ПСИХОЛОГІЧНІ ЗАСАДИ СИСТЕМНОГО РОЗВИТКУ ІНФОРМАЦІЙНОЇ КУЛЬТУРИ МАЙБУТНІХ СОЦІАЛЬНИХ ПЕДАГОГІВ - Рацул, Олександр (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Статтю присвячено висвітленню психологічних засад системного розвитку інформаційної культури майбутніх соціальних педагогів. Зокрема, зосереджено увагу на проблемі психологічного забезпечення використання інформаційно-комунікаційних технологій як ефективного засобу системного розвитку інформаційної культури майбутніх соціальних педагогів. Виокремлено чотири можливих рівня навченості (впізнавання об’єктів і явищ за їх ознаками; репродуктивна діяльність із відтворення інформації; використання знань для продуктивної практичної діяльності за раніше засвоєним зразком; продуктивна діяльність). Статья посвящена освещению психологических основ системного развития информационной культуры будущих социальных педагогов. В частности, внимание сосредоточено на проблеме психологического обеспечения использования информационно-коммуникационных технологий как эффективного средства системного развития информационной культуры будущих социальных педагогов. Выделены четыре возможных уровня обученности (узнавание объектов и явлений по их признакам; репродуктивная деятельность по воспроизводству информации; использование знаний для продуктивной практической деятельности по ранее усвоенным образцам; продуктивная деятельность). The article deals with highlighting of psychological basics of the systemic development of future social pedagogists’ informational culture. In particular, attention is focused on the problem of psychological support of the usage of informational-and-communicational technologies as an effective tool for the systemic development of future social pedagogists’ informational culture. Besides, it is stated that social in its grounds and pedagogical in its content conception of universal development of future social pedagogists’ individualities which defines the target instructions of educational activities, including the conditions of informational-and-communicational studies, urgently requires an appeal to psychological problems. Four possible levels of training (recognition of objects and events in terms of their features; reproductive activities in the reproduction of information; the usage of knowledge for productive practice in previously learned patterns; productive activities) are identified.